Cockfosters stories - Simpson, Helen 1957- (Knopf, 2017)
"A wickedly wry, tender new collection from one of our finest internationally acclaimed short story writers. Nine virtuoso stories that take up the preoccupations and fixations of time's passing and of middle age and that take us from today's London and Berlin to the wild west of the USA and the wilder shores of Mother Russia; stories finely balanced between devastation and optimism. In the title story, long-ago school pals take the London Underground to the end of the Piccadilly line...Cockfosters Station...to retrieve a lost pair of newly prescribed bifocals ("The worst thing about needing glasses is the bumbling," says Julie. "I've turned into a bumbler overnight. Me! I run marathons!"); each station stop prompting reflections on their shared past, present, and possible futures. In "Erewhon," a gender-role flip: after having sex with his wife, who has turned over and instantly fallen asleep, a man lies awake fretting about his body shape, his dissatisfaction with sex, his children, his role in the marriage. In "Kythera," lemon drizzle cake is a mother's ritual preparation for her (now grown) daughter's birthday as she conjures up memories of all the birthday cakes she has made for her, each one more poignant than the last; this new cake becoming a memento mori, an act of love, and a symbol of transformation... And in "Berlin," a fiftysomething couple on a "Ring package" to Germany spend four evenings watching Wagner's epic, recalling their life together, reckoning with the husband's infidelity, the wife noting the similarity between their marriage and the Ring Cycle itself: "I'm glad I stuck it out but I'd never want to sit through it again.""...
Keywords: FICTION / Literary / bisacsh; FICTION / Contemporary Women / bisacsh; FICTION / Short Stories (single author) / bisacsh; FICTION / Literary; FICTION / Contemporary Women; FICTION / Short Stories (single author); Fiktionale Darstellung